2006
DOI: 10.1103/physrevd.74.106008
|View full text |Cite
|
Sign up to set email alerts
|

Holographic melting and related properties of mesons in a quark-gluon plasma

Abstract: We analyze mesons at finite temperature in a chiral, confining string dual. The temperature dependence of low-spin as well as high-spin meson masses is shown to exhibit a pattern familiar from the lattice. Furthermore, we find the dissociation temperature of mesons as a function of their spin, showing that at a fixed quark mass, mesons with larger spins dissociate at lower temperatures. The Goldstone bosons associated with chiral symmetry breaking are shown to disappear above the chiral symmetry restoration te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
292
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(336 citation statements)
references
References 35 publications
35
292
3
Order By: Relevance
“…The n = 3 metric, known as Sakai-Sugimoto metric [12] (modulo details of the compact 5 dimensional manifold which we ignore here) in the high temperature phase [14], is the near- The Nambu-Goto action is given by…”
Section: General Setupmentioning
confidence: 99%
“…The n = 3 metric, known as Sakai-Sugimoto metric [12] (modulo details of the compact 5 dimensional manifold which we ignore here) in the high temperature phase [14], is the near- The Nambu-Goto action is given by…”
Section: General Setupmentioning
confidence: 99%
“…6.5 above) at finite temperature. That model also displays a first-order meson melting transition as described in [195,211]. Additional finite density studies can be found in [173,174,[212][213][214][215][216][217].…”
Section: More Thermodynamicsmentioning
confidence: 99%
“…The properties of heavy-light mesons at finite temperature are determined in [195]. A long D3-D7 string describes a heavy deconfined quark and the energy loss and wake produced by such a string dragged through the plasma has been studied in [196][197][198][199].…”
Section: Mesons In the Ads Black-hole Backgroundmentioning
confidence: 99%
“…The behavior of low-spin mesons, which we will focus on in this paper, is described by small fluctuations of the flavor D8-branes, which can be treated (for N f ≪ N c ) as probes embedded in the D4-brane background. The meson spectra at zero chemical potential and non-zero temperature have been analyzed in [31].…”
Section: Jhep02(2008)071mentioning
confidence: 99%